Effects of Allium mongolicum regel essential oil supplementation on growth performance, nutrient digestibility, rumen fermentation, and bacterial communities in sheep - Yaxing, Zhao; Erdene, Khas; Zhibi, Bao; Changjin, Ao; Chen, Bai (Frontiers in Veterinary Science, 2022)
The objectives of this research were to investigate the effects of Allium mongolicum Regel essential oil on growth performance, nutrient digestibility, rumen fermentation and bacterial communities in sheep. Twenty sheep were randomly divided into two groups. The sheep were randomly divided into two dietary groups with 10 replicates each: (1) a basal diet without AMO as the control group (n=10) and (2) a basal diet supplemented with 40 mg/kg AMO as the AMO group (n=10). The average daily gain (ADG) was increased (P < 0.05), and the feed conversion ratio (FCR) was reduced (P < 0.05) in the AMO group compared with the control. The ruminal acetate, propionate, total volatile fatty acids (TVFA), and microbial protein (MCP) were higher (P < 0.05) in the AMO group than in the control. Moreover, ruminal pH and ammonia nitrogen (NH3-N) were lower (P < 0.05) in the AMO group than in the control. The relative abundances of the phylum levels of Firmicutes, Actinobacteriota and Verrucomicrobiota were higher (P < 0.05) in the AMO group than in the control, and the relative abundances of Bacteroidetes and Spirochaetota were lower (P < 0.05) in the AMO group than in the control. The relative abundance of Prevotella and Prevotellaceae_UCG-003 at the genus level was increased (P < 0.05) in the AMO group compared with the control; however, the relative abundance of Succiniclasticum, Norank_f__F082, Christensenellaceae_R-7_group and Norank_f__Muribaculaceae was decreased (P < 0.05) in the AMO group compared with the control. The activities of cellulase, α-amylase and proteinase were higher (P < 0.05) in the AMO group than in the control. Apparent digestibility of dry matter (DM) and crude protein (CP) were increased (P < 0.05) in the AMO group compared with the control. In conclusion, AMO supplementation has the potential to improve growth performance. Moreover, supplementation with AMO improved nutrient digestibility, rumen fermentation and bacterial communities in the rumen of sheep.